Odobenus rosmarus - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Odobenus rosmarus (Linnaeus, 1758). Syst. Nat., 10th ed., 1:38. TYPE LOCALITY: "intra Zonam arcticam Europae, Asiae, Americae". DISTRIBUTION: Arctic seas: south as far as New England (USA), Great Britain, Scandinavia, Pribilof Isis, and Honshu (Japan) at least occasionally. STATUS: CITES - Appendix III (Canada); IUCN - Insufficiently known as O. r. laptevi. SYNONYMS: arcticus Pallas, 1811; cookii Fremerij, 1831; divergens liliger, 1815; obesus liliger, 1815; orientalis Dybowski, 1922. COMMENTS: Reviewed by Fay (1985, Mammalian Species, 238). Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 326, DOI: 10.5281/zenodo.7359191